INTERRELATION OF PRIONS WITH NON-CODING RNAS - R. N. Mustafin; E. K. Khusnutdinova (Вавиловский журнал генетики и селекции)
Prions are alternative infectious conformations for some cellular proteins. For the protein PrPC (PrP – prion protein, С – common), a prion conformation, called PrPSc (S – scrapie), is pathological. For example, in mammals the PrPSc prion causes transmissible spongiform encephalopathies accumulating in the brain tissues of PrPSc aggregates that have amyloid properties. MicroRNAs and long non-coding RNAs can be translated into functional peptides. These peptides can have a regulatory effect on genes from which their non-coding RNAs are transcribed. It has been assumed that prions, like peptides, due to the presence of specific domains, can also activate certain non-coding RNAs. Some of the activated non-coding RNAs can catalyze the formation of new prions from normal protein, playing their role in the pathogenesis of prion diseases. Confirmation of this assumption is the presence of the association of alleles of microRNA with the development of the disease, which indicates the role of the specific sequences of noncoding RNAs in the catalysis of prion formation. In the brain tissues of patients with prion diseases, as well as in exosomes containing an abnormal PrPSc isoform, changes in the levels of microRNA have been observed. A possible cause is the interaction of the spatial domains of PrPSc with the sequences of the non-coding RNA genes, which causes a change in their expression. MicroRNAs, in turn, affect the synthesis of long non-coding RNAs. We hypothesize that long noncoding RNAs and possibly microRNAs can interact with PrPC catalyzing its transformation into PrPSc. As a result, the number of PrPSc increases exponentially. In the brain of animals and humans, transposon activity has been observed, which has a regulatory effect on the differentiation of neuronal stem cells. Transposons form the basis of domain structures of long non-coding RNAs. In addition, they are important sources of microRNA. Since prion diseases can arise as sporadic and hereditary cases, and hereditary predisposition is important for the development of pathology, we hypothesize the role of individual features of activation of transposons in the pathogenesis of prion diseases. The activation of transposons in the brain at certain stages of development, as well as under the influence of stress, is reflected in the peculiarities of expression of specific non-coding RNAs that are capable of catalyzing the transition of the PrPC protein to PrPSc. Research in this direction can be the basis for targeted anti-microRNA therapy of prion diseases.